A cohort study of treatment outcomes after radiotherapy in vulva carcinoma patients. Issue 2 (2nd July 2020) - Goba-Mjwara, T; Simonds, H
Abstract : Background: Carcinoma of the vulva is an uncommon tumour. For locally advanced vulval cancer with proximity to the urethra or anal margin, surgery often involves exenteration with colostomy or urinary diversion, which results in significant physical and psychological morbidity. The use of neoadjuvant or primary chemoradiation is an acceptable treatment option for those patients deemed unsuitable for primary surgery in advance. In addition, if the patient has poor locoregional control this has a significant impact on quality of life following treatment. This study aimed to evaluate radiotherapy curative and palliative treatment outcomes for patients in a single institution. Methods: A quantitative retrospective cohort analysis of all women diagnosed with vulval cancer managed in a single institution was undertaken. Eligible patients included patients with vulval carcinoma referred for radiotherapy (RT)—primary, adjuvant and palliative. Demographic and clinical data, treatment time and radiotherapy fractionation were noted. The primary end-points were local control (LC) and overall survival (OS). Results: Forty-two patients were referred during the study period. Among the 33 evaluable patients, all patients completed treatment. At 12 months' follow-up, 20 women were alive (4 with evidence of recurrent/persistent disease) and 13 had died (4 with documented recurrent disease). At the time of data analysis, 22 patients received curative treatment: definitive chemoradiation or radiation alone ( n = 17) or adjuvant RT ( n = 5). Of the 22 patients, 11 were in remission, 8 had been lost to follow-up, and 3 had documented local recurrence. In total, 11 patients received palliative treatment. The overall survival at 12 months for the patients who received primary surgery followed by adjuvant radiotherapy was 100%. There was, however, no significant difference between the survival for the definitive CRT/RT (57.5%) and the high-dose palliative RT (49.1%) groups. However, the dose of radiotherapy was significant; women who received a total dose of radiotherapy greater than 60 Gy had improved local control compared with those who received a total dose of less than 45 Gy. Conclusion: Surgery followed by adjuvant treatment had a superior overall survival outcome compared with definitive chemoradiation or radiotherapy alone in this small cohort, reflecting poorer outcomes for advanced disease.